THE INFLUENCE OF ENGLISH LANGUAGE PROFICIENCY ON STUDENTS’ CAREER PROSPECTS - Toshmanova Sevinch Shodiyor qizi,; Hasanova Sevinch Hotam qizi,; Miyliyeva Xilola Sayfidinovna, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract: In today’s increasingly interconnected world, English functions as the dominant  language  of  global  communication,  higher  education,  research,  and commerce. With the rapid growth of globalization, the need for professionals who can communicate effectively in English continues to expand. This paper analyzes the role of English language proficiency in shaping students’ career prospects, employability, professional  growth,  earning  potential,  and  access  to  international  education.  The findings emphasize that strong English skills improve students’ competitiveness in the job market and prepare them for success in a global environment.